Dear participants of the Congress, esteemed scholars, and guests (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
It is a great honor for us that the materials of this large-scale academic event “Traditional Culture and Art: Problems of Preservation and Development”, held within the framework of the festival —  are being published in a special edition of the scientific journal Proceedings of the National Academy of Sciences of the Kyrgyz Republic. We are confident that this collection will provide opportunities for in-depth analysis of current research issues in the field of art, help identify new directions, and foster the exchange of experience. This year marks 21 years since April 25 was officially recognized as the Day of Traditional Music in the history of independent Kyrgyzstan. Since 2004, significant efforts have been made in the country to preserve, promote, and develop traditional musical art. A resolution of the Jogorku Kenesh (Parliament) on the celebration of the National Day of Traditional Music of the Kyrgyz Republic and a Presidential Decree declaring the Day of the Komuz have been adopted.
Keywords: -